Thyroid hyalinizing trabecular adenoma with a high thyroglobulin level: a case report. Issue 7 (31st July 2021) - Katano, Hirofumi; Hasegawa, Hisashi; Matsuzaki, Hiroumi; Oshima, Takeshi; Tang, Xiaoyan
Abstract: Thyroid hyalinizing trabecular adenoma (HTA) is a rare and borderline tumor of follicular origin. It is characterized by a trabecular growth pattern and marked intratrabecular hyalinization. Excessively elevated thyroglobulin levels have not been reported previously in cases without bilateral lung metastases. Here, we present a case of a 54-year-old woman with chronic thyroiditis with a 50-mm tumor in the left lobe of the thyroid gland, which was observed on ultrasonography. Her thyroglobulin level was found to be elevated at 684 ng/ml. Since fine needle aspiration cytology could not exclude possible malignancy, she underwent thyroid lobectomy; the final diagnosis was thyroid HTA. Two weeks after resection, her thyroglobulin level showed negative conversion. To our knowledge, this is the first report of a patient with a thyroid HTA exhibiting a thyroglobulin level as high as that for a patient with hyalinizing trabecular carcinoma.